2013
DOI: 10.1111/1750-3841.12252
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evaluation of Dry‐fermented Sausage Containing Ground Deodorized Yellow Mustard

Abstract: Ground deodorized yellow mustard is used as a binder and meat protein substitute in cooked processed meat products. Recent studies have shown that it has the potential to be used in uncooked processed meat products because of its natural antimicrobial properties. In the present study, ground deodorized yellow mustard was added to uncooked dry-fermented sausage during manufacture at 1% to 4% (w/w) and analyzed for its effects on starter cultures, physico-chemical properties, and consumer acceptability. Mustard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Microencapsulated allyl isothiocyanate (AIT) at 500 ppm gave 4.75-log reductions of E. coli O157:H7 in DFS 28 days after processing, >3 log more than control DFS [261]. Deodorized mustard powder, containing AIT as an antimicrobial ingredient, provided 5-log reduction of E. coli O157:H7 28 days after processing when used at 4% in DFS [262][263][264][265][266]. However, mustard levels needed to cause the required inhibition of E. coli O157:H7 reduced consumer acceptability of the sausages [265].…”
Section: Preservatives For Enhancedmentioning
confidence: 99%
See 1 more Smart Citation
“…Microencapsulated allyl isothiocyanate (AIT) at 500 ppm gave 4.75-log reductions of E. coli O157:H7 in DFS 28 days after processing, >3 log more than control DFS [261]. Deodorized mustard powder, containing AIT as an antimicrobial ingredient, provided 5-log reduction of E. coli O157:H7 28 days after processing when used at 4% in DFS [262][263][264][265][266]. However, mustard levels needed to cause the required inhibition of E. coli O157:H7 reduced consumer acceptability of the sausages [265].…”
Section: Preservatives For Enhancedmentioning
confidence: 99%
“…Deodorized mustard powder, containing AIT as an antimicrobial ingredient, provided 5-log reduction of E. coli O157:H7 28 days after processing when used at 4% in DFS [262][263][264][265][266]. However, mustard levels needed to cause the required inhibition of E. coli O157:H7 reduced consumer acceptability of the sausages [265]. Other ingredients tested include the use of lactoferrin [234] and diacetyl [267].…”
Section: Preservatives For Enhancedmentioning
confidence: 99%
“…Shear value was increased during ripening due to drying of moisture form the fermented ham ( p <0.05), however, no differences were observed between two batches ( p >0.05). Li et al (2013) reported that dry fermented sausage containing ground deordorized yellow mustard, the potential antioxidant, had lower shear value than the control, and increased the shear value with increased ripening for 28 d. Popp et al (2013) reported that turkey fermented sausages with dark, normal, and pale muscle had similar shear values and concluded that turkey meat could be used to manufacture the fermented sausages without quality defects. Cholesterol contents of batch A and B were 70.16 and 67.95 mg/100 g, respectively, and were similar to each other.…”
Section: Resultsmentioning
confidence: 99%
“…In further work, sensory studies should examine the consumer acceptability of dry sausages containing mustard with measurable residual myrosinase as well as those made with deoiled mustard meal. In previous work, consumer acceptability was negatively influenced by the detection of mustard flavor notes in sausages with ≥3% deodorized mustard powder (Li et al, 2013). Moreover, work is needed to explore the antimicrobial activity of deoiled mustard meal at concentrations b2% (w/w).…”
Section: Resultsmentioning
confidence: 99%
“…Work has been done using various concentrations (2 to 6% w/w) of hot (spicy) and deodorized (organoleptically neutral) yellow mustard, and results have been promising but somewhat variable (Cordeiro et al, 2013;Graumann and Holley, 2008;. With 4 to 6% of deodorized mustard from 18 to 38 d was necessary to satisfy the North American E. coli O157:H7 reduction requirements, but the normal production period for commercial products of the size tested (0.5 kg) is 35 d. In addition, at deodorized mustard concentrations ≥ 3%, consumers were able to detect its presence in these products (Li et al, 2013). The inconsistency in the rate of E. coli O157:H7 elimination observed in the previous studies raised questions about reasons for variability in the antimicrobial action of mustard.…”
Section: Introductionmentioning
confidence: 99%